2017
DOI: 10.1039/c7cs00684e
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of transient speciesviaanion photodetachment

Abstract: The dynamics of chemical reactions are often governed by transient species, including the transition state for activated bimolecular reactions. Such transient species are difficult to study experimentally, but it has proven valuable to prepare and probe transition-state dynamics by the photodetachment of anions with an equilibrium geometry similar to the neutral transition state. In this review, recent experimental advances in photoelectron and photoelectron-photofragment coincidence spectroscopy are discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 168 publications
0
43
0
Order By: Relevance
“…It is well known that small molecular anionic systems can undergo a second type of dissociation process induced by UV excitation, in which the system is vertically placed on the reaction coordinate of the neutral radical species generated by electron detachment. 11 For example, dissociative photodetachment of cold deprotonated acetic acid (CH3COO  ) has been studied using photoelectron-photofragment coincidence spectroscopy, giving a complete description of the (CH3COO •  CH3 • + CO2) rearrangement reaction. 12 The dissociative photodetachment mechanism has also been described in deprotonated aryl carboxylic acids, such as benzoic or naphthoic anions, by measurement of the kinetic energy of the neutral species involved in the reaction, that is the remaining unfragmented radical (C6H5COO • or C10H7COO • ) together with the respective photoproducts (C6H5 • + CO2) or (C10H7 • + CO2).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that small molecular anionic systems can undergo a second type of dissociation process induced by UV excitation, in which the system is vertically placed on the reaction coordinate of the neutral radical species generated by electron detachment. 11 For example, dissociative photodetachment of cold deprotonated acetic acid (CH3COO  ) has been studied using photoelectron-photofragment coincidence spectroscopy, giving a complete description of the (CH3COO •  CH3 • + CO2) rearrangement reaction. 12 The dissociative photodetachment mechanism has also been described in deprotonated aryl carboxylic acids, such as benzoic or naphthoic anions, by measurement of the kinetic energy of the neutral species involved in the reaction, that is the remaining unfragmented radical (C6H5COO • or C10H7COO • ) together with the respective photoproducts (C6H5 • + CO2) or (C10H7 • + CO2).…”
Section: Introductionmentioning
confidence: 99%
“…Though seemingly simple species, fundamental questions regarding the gas-phase structure of deprotonated amino acids and, in particular, the neutral radicals issued from their electron detachment remain unanswered to date. The stability of small dehydrogenated acid radicals has been studied through coincidence techniques 1 . In particular, it has been shown that the simplest, acetyloxyl, loses CO 2 upon photodetachment, with a small barrier (0.1eV)calculated for CO 2 loss 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Studying the dynamics or kinetics of such complexes in the gas phase has typically required ultrafast (13)(14)(15)(16)(17) or stabilizing collisional (18)(19)(20) techniques. Structural investigations of these complexes have been previously obtained by photodetachment (21,22), photoabsorption ( 23), or photodissociation (24). On the basis of the Rice-Ramsperger-Kassel-Marcus (RRKM) theory, the lifetime of an intermediate complex is given by t c ¼ 2pr c =N o , Fig.…”
mentioning
confidence: 99%